The Relationship Between the Exchange Rate, Terms of Trade and Employment in Turkey (2022)
The objective of this paper is to analyze the impact of real exchange rate (RER) on employment and real wage using quarterly disaggregated data (ISIC Rev 4 classification) composed of 19 industries in Turkey from 2010 to 2017. This study employed the Fixed Effect Model, where industry-specific effects are used to control heterogeneity within the industry. The results reflect that currency appreciation negatively affects employment, though insignificant, whereas it has a remarkably positive impact on real wage. Although the terms of trade have no visible impact on employment and real wages, the study uniquely finds that the effects of the larger industries on employment are distinctly adverse. Nevertheless, the interaction between currency appreciation and the top 25 per cent larger industries indicates a moderate increase in employment. The findings reflect that the appreciation of the domestic currency causes employment to decrease at the industry level. The originality of this paper includes the effects of the terms of trade and interaction with currency appreciation in larger industries using the Fixed Effect Model approach.